Analisis Persepsi dan Harapan Mahasiswa Terhadap Implementasi SKPI dengan Sistem Kredit Poin di Fakultas Ekonomi Universitas Negeri Padang - Ririn Jaslita; Armiati S (Jurnal Ecogen, 2019)
This study aims to explain how the socialization and implementation of filling the SKPI at FE UNP. Can be seen from the four indicators filling SKPI namely 1) academic activities 2) student activities 3) compulsory activities and 4) optional activities in terms of the perceptions and expectations of FE UNP students totaling 510 people. This type of research is a descriptive study with a survey approach that uses primary data as research data and was obtained from a questionnaire filled out by FE 2015 UNP students. The sample of this study was 84 students. Sampling with Proportional random sampling. The data analysis technique used is descriptive analysis and gap analysis (gap / discrepancy between perception and expectations) using a Cartesian diagram. The analysis shows that the four indicators filling SKPI with credit points in the category are quite effective in terms of students' perceptions and expectations. The results of the analysis with the Importance performance matrix and Cartesian diagram of all indicators in the student satisfaction index table show that students perceive all indicators lower than expected. All four indicators need to be improved. The results showed that the implementation of SKPI filling with the credit system at FE UNP was quite effective by students. While the expectations of the Faculty of Economics students were in the high category. Therefore, it is recommended to the Faculty Leaders to conduct a review or to socialize the application of the SKPI with a credit system on indicators of student activities and choices. It is expected that the Faculty Leaders to improve the implementation of SKPI filling at the Faculty of Economics, State University of Padang in terms of 1) Socialization of filling SKPI with credit points systematically, comprehensively and continuously 2) Developing student activities based on soft skills, as a means of developing student character 3) updating Circular Letters and Student Activity Handbook 2015. Students are expected to obey the rules of Circular and Guidebook and participate in developing their potential in non-academic activities that support academic achievement for added value and readiness of students to enter the workforce. Keyword: SKPI, kredit poin, soft skills, kemahasiswaan.